Multi-functional voltage and current based enhancement of power quality in grid-connected microgrids considering harmonics - Ehsan Akbari; Abbas Zare Ghaleh Seyyedi (Heliyon, 2024)
The introduction of a renewable energy source (RES) based multi-functional grid-tied inverter (MFGTI) stands as a favorable remedy for addressing power quality concerns within distributed generation (DG) systems and microgrids. Nonetheless, the effectiveness of a traditional MFGTI will be restricted in addressing power quality issues based on voltage. The presented research proposes a novel structure for MFGTI to enhance power quality concerns associated with voltage, current, and harmonic distortions resulting from both grid and loads. Based on this strategy, the introduced MFGTI can be linked with the grid by bidirectional switches either in a parallel or series. This feature provides various operational conditions in response to diverse disruptions in the grid. To effectively adjust the voltage, current and voltage reduction are determined through mathematical analysis, considering both the grid conditions and the load requirements. Furthermore, this strategy offers different compensation strategies, control schemes, and transition modes in the MFGTI. The major disturbances such as unbalanced and balanced voltage swell/sag, harmonics, and interruption are compensated. The shunt compensation controller is based on a second order sequence filter (SOSF) to provide the load current active component. A damping PI regulator based series compensation controller is presented for the voltage swell/sag reduction. Moreover, a new three level hierarchical control is proposed in which a droop control for compensating the interruption and a decouple dual synchronous reference frame (DDSRF) for compensating the unbalanced voltage sag/swell are utilized. The simulations in the MATLAB/SIMULINK show that using the proposed compensation strategies, the proposed MFGTI can compensate effectively the different disturbances through changing the transition states by the proposed algorithm based bidirectional switches.